Effects of lean combustion on bioethanol-gasoline blends using turbocharged spark ignition engine - S. M., Rosdi; R., Mamat; Azri, Alias; Sudhakar, K. (Universiti Malaysia Pahang, 2021)
Liquid alternative fuels have been utilised as engine fuel since the 19th century. For several alternative fuels, bioethanol is well-known as the most suited friendly, alternative-product based and renewable for use in spark-ignition (SI) engines. In addition, it is well known that bioethanol has higher evaporation of heat, research octane number and flammability of temperature; therefore, it has a greater influence on performance and lower emission. In this study, the effect of gasoline fuel RON95 (G) was blended into bioethanol fuel (E10, E20 and E30) to investigate the engine combustion, performance and emission. The engine used was 1.8L Mitsubishi, four-cylinder, four-stroke, multipoint port injection and turbocharger SI. The engine speed used was 1000-3000 rpm at 10-40% load with wide-open throttle (WOT). The results showed that bioethanol addition to gasoline increases the brake torque at a higher load. The mass fraction burn (MFB) and coefficient of variation (COV) blend fuel and main fuel are comparable to each other. The brake specific fuel consumption (BSFC) significantly increases when engine speed increases. The emission of nitrogen oxide (NOx), carbon monoxide (CO), and hydrocarbon (HC) emissions reduced dramatically compared to gasoline fuel. Indeed, bioethanol-gasoline fuel allows the engine utilised in low proportion to increase engine performance and lower engine emission.